Design factors promoting the benefits of an edible campus in China - Ding, Xiaoying; Zhao, Shuqi; Yue, Xiaopeng; Xing, Yangang; Zhao, Zhiyuan (Frontiers in Sustainable Food Systems, 2024)
Currently, most university campuses in China are plagued by issues such as high food demand, imbalanced diets, serious food waste and poor environmental quality. Research has shown that the multiple benefits of an edible campus, which may also be referred to as a school garden or farm catering to various educational levels, can help alleviate the aforementioned problems. However, there is limited research on how to promote the benefits of an edible campus through design. Therefore, taking the South Campus of Hebei University of Technology in China as an example, this paper aims to explore the correlation between design and benefits of an edible campus. The design factors and benefit factors related to an edible campus are extracted through literature search. The design preferences and benefit predictions are obtained through 261 questionnaire surveys and interviews with 30 participants. During the statistical analysis phase, principal component analysis and multiple regression analysis are applied to analyze the correlation between design factors and benefit factors. The results indicate: (1) The design factors of an edible campus can be categorized into seven categories: spatial location, spatial carrier, size, space function, facility configuration, planting and crop varieties, and technology application. (2) The benefits of an edible campus include environmental education, physical and mental health, social interaction, ecological protection, and economic output. (3) There are significant differences in design factors that positively or negatively correlate with different benefits. Among them, the strongest positive correlation exists between planting function and the five benefits, followed by central landscape and container planting. Furthermore, the causes behind the correlation between design factors and benefit factors are analyzed, and design strategies for an edible campus under different benefit orientations are proposed. The findings of this study can contribute to the sustainable development of university campuses in China.